Critical Analysis of Contemporary Issues in Nursing Care Delivery - Alquraywi, Jazalh Mohammed; Alshamrani, Jameela Mohammed; Albattal, Maram Ibrahim; Alyami, Fares Mansour; Sharahili, Hana Hassan; Alduraibi, Latifah Abdullah; Asiri, Sbah Abdullah; Alnahdi, Norah Abdullah; AlRuways, Rania bandar; alyiyfah, Monera khaled (Journal of Ecohumanism, 2024)
Delivering nursing care is an essential part of the health system. However, this model experiences a set of modern-day challenges which impact it positively or negatively. This paper assesses and critiques several important areas that affect nursing care: short staffing levels, increased understanding of patients, application of technology in the healthcare sector, and changes in the nurse's role in working with other practitioners. Marshalling considerations from the global context, the paper explores how factors impact the differentiation of patient outcomes, nurses' perspectives, and healthcare system effectiveness. The challenges can be resolved through policy change, improving staff training and development and addressing service provision and configuration. Possible case descriptions and analyzing statistical information are used to encourage the analysis. The review finally provides strategies for work practice enhancement for nursing care delivery, including consideration of workforce, reform of nurse education, and adoption of technologies in patient care.